Venlafaxin-associated post-ictal asystole during electroconvulsive therapy - Kranaster, Laura; Janke, Christoph; Frölich, Lutz; Sartorius, Alexander (Pharmacopsychiatry, 2012)
While post-stimulus asystoles occur quite often during electroconvulsive therapy (ECT) post-ictal or post-seizure sinus bradycardias or even asystoles are rare events. We report the case of an 82-year-old female patient with a current major depressive episode, who developed the rare event of a post-ictal asystole of 6 s and 4 ventricular escape beats during ECT. In the past this patient with a bipolar disorder and mild Alzheimer’s disease had already been frequently treated with ECT with good success and no adverse events. Relevant comedication was venlafaxin, quetiapine, donepezil and clonidine, anesthesia was performed with ketamine and succinylcholine. Concurrent medication was completely unchanged compared to previous ECT sessions with the exception of venlafaxine, presumably at high serum levels. In summary, in line with some already existing reports, we expect the noradrenergic action of venlafaxin to have contributed substantially to the post-ictal asystole and want to indicate that the combination of ECT and venlafaxin might be harmful - especially in the elderly population.